Variation in MICA and MICB genes and enhanced susceptibility to paucibacillary leprosy in South India. - Tosh, K; Ravikumar, M; Bell, J; Meisner, S; Hill, A; Pitchappan, R (2006)
In a study of mainly paucibacillary leprosy-affected sib-pair families from South India, in addition to the expected associations with the HLA-DRB1 locus, we have identified significant association with a functional variant of the MICA gene as well as a microsatellite in the flanking region of the MICB gene. The associations with MICA and MICB cannot be accounted for by linkage disequilibrium with the HLA class II locus indicating a role in genetic susceptibility to leprosy that is independent of HLA-DRB1. Previous studies have shown that MICA and MICB are expressed on the surface of cells in response to infection, where they are recognized by the NKG2D receptor on gammadelta T cells, CD8+ alphabeta T cells and natural killer cells, all of which contribute to defense against mycobacteria. The MICA*5A5.1 allele, associated here with leprosy susceptibility, encodes a protein lacking a cytoplasmic tail providing a possible mechanism for defective immune surveillance against mycobacteria.